How to Evaluate Value Proposition - Amurjuev, Oleg (Problem As Inspiration: A Journal of the York Entrepreneurship Development Institute, 2018)
One of the first questions investors ask while discussing an investment opportunity is “what is a value proposition of your project/product/services, i.e. what a value you are creating for your customers?” The answer to this question is not so simple as it could seem. How to define the value, what criteria and metrics should be used to substantiate value – those issues are discussed in the article. Also: how to create and deliver the value which would be sensitive to prospective customers and markets – that was touched in the proposed paper.